GEOTAGE: GEOLOGICAL SHAREWARE APPLICATION FOR GEOLOGY OBJECT - Tara Shinta Dewi, at. al (Departmen Teknik Geologi, 2015)
Indonesia has complete geological objects such as outcrops (igneous rock, sedimentary rock, metamorphic rock and pyroclastic rock), mineral deposit, active and non-active volcano also geoheritage as Indonesia precious assets. However, there is obstacle that the lack of specific application to record coordinate location of geological objects and Geotage present to solve the obstacle. Geotage was built by java programing language with eclipse tool and server database using MYQSL. Geotage is the search and discovery of local mobile application service which provides personal local search experience for its users. Geotage provide a web-based control panel where users can find outcrop geology and geological heritage around the user's location. This application allows remote GPS to make it easier to find your device and view the location on a map. Geotage can be free downloaded via smartphone. After downloaded, user have to register for using all Geotage features. By paying attention to where users go, registered user can upload coordinate location, description and picture of the geological object. These data will be stored in Geotage server and can be shared each other users. Then, Geotage’s user can also access geological object data from other users integrated to social media for discussed. Hopefully, all of Indonesia precious geological objects can be recorded in Geotage so they can be recognized and preserved by us.